Examining the Child Care Cliff Effect in a Rural Setting - Susan Roll (Social Work and Society)
The purpose of this study was to better understand the experience of families accessing government subsidized child care support in a largely rural California county.  Of interest was the benefits cliff faced by families when they are offered opportunities for additional wages that will put them over the income limit for subsidized child care - a phenomenon known as the cliff effect.  Survey results show that 35% of families report facing the child care cliff.  Qualitative interviews with a subset of these families revealed several themes, including administrative hassles and struggling with basic needs. Unique to this study were issues for families with multiple health problems and transportation challenges. With the limited research on low-income families living in rural settings, these results add to recent discussions of unequal access to care, and to the newly emerging understanding of child care deserts.